Nuanced role for dendritic cell intrinsic IRE1 RNase in the regulation of antitumor adaptive immunity - Flores-Santibañez, Felipe; Rennen, Sofie; Fernández, Dominique; De Nolf, Clint; Van De Velde, Evelien; Gaete González, Sandra; Fuentes, Camila; Moreno, Carolina; Figueroa, Diego; Lladser, Álvaro; Iwawaki, Takao; Bono, María Rosa; et al. (Frontiers in Immunology, 2023)
In cancer, activation of the IRE1/XBP1s axis of the unfolded protein response (UPR) promotes immunosuppression and tumor growth, by acting in cancer cells and tumor infiltrating immune cells. However, the role of IRE1/XBP1s in dendritic cells (DCs) in tumors, particularly in conventional type 1 DCs (cDC1s) which are cellular targets in immunotherapy, has not been fully elucidated. Here, we studied the role of IRE1/XBP1s in subcutaneous B16/B78 melanoma and MC38 tumors by generating loss-of-function models of IRE1 and/or XBP1s in DCs or in cDC1s. Data show that concomitant deletion of the RNase domain of IRE1 and XBP1s in DCs and cDC1s does not influence the kinetics of B16/B78 and MC38 tumor growth or the effector profile of tumor infiltrating T cells. A modest effect is observed in mice bearing single deletion of XBP1s in DCs, which showed slight acceleration of melanoma tumor growth and dysfunctional T cell responses, however, this effect was not recapitulated in animals lacking XBP1 only in cDC1s. Thus, evidence presented here argues against a general pro-tumorigenic role of the IRE1/XBP1s pathway in tumor associated DC subsets.